Patient safety: understanding human error in intensive nursing care - Sabrina da Costa Machado Duarte; Marluci Andrade Conceição Stipp; Maria Manuela Vila Nova Cardoso; Andreas Büscher (SciELO, 2018)
ABSTRACT Objective: To analyze the active failures and the latent conditions related to errors in intensive nursing care and to discuss the reactive and proactive measures mentioned by the nursing team. Method: Qualitative, descriptive, exploratory study conducted at the Intensive Care Unit of a general hospital. Data were collected through interviews, participant observation and submitted to lexical analysis in the ALCESTE® software and to ethnographic analysis. Results: 36 professionals of the nursing team participated in the study. The analysis originated three lexical classes: Error in intensive care nursing; Active failures and latent conditions related to errors in the intensive care nursing team; Reactive and proactive measures adopted by the nursing team regarding errors in intensive care. Conclusion: Reactive and proactive measures influenced the safety culture, in particular, the recognition of errors by professionals, contributing to their prevention, safety and quality care.